Polymer composition, extruded polymer composition, article comprising the composition, and method of making the article

By using polymer compositions of polyamide 6, maleic anhydride grafted polypropylene and polypropylene compositions, the problem that a single material in the prior art is difficult to provide good polar and non-polar barrier properties and heat resistance. A high performance polymer composition in extruded and optionally formed articles is achieved, and the performance remains good after recovery.

CN119463485APending Publication Date: 2025-02-18QUINLYTE HLDG BV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411061960.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-08
Filing Date
2024-08-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to provide a single material that can exhibit good polarity and non-polarity barrier properties, as well as heat resistance in both barrier packaging and non-barrier packaging, and maintain good performance after recovery.

Method used

Using a polymer composition containing polyamide 6, maleic anhydride grafted polypropylene and polypropylene composition, the ratio and structure of each component are adjusted to form good polarity and non-polarity in extruded and optionally formed articles. Polar barrier properties polymer composition.

Benefits of technology

The high heat resistance performance in extruded and optionally formed articles is achieved and good performance is maintained after recycling, solving the problem that a single material is difficult to meet multiple performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004978170730000091
    Figure BDA0004978170730000091
  • Figure BDA0004978170730000181
    Figure BDA0004978170730000181
  • Figure BDA0004978170730000182
    Figure BDA0004978170730000182
Patent Text Reader

Abstract

The present invention relates to a polymer composition, an extruded polymer composition, an article comprising the composition, and a method of making the article. The present invention relates to a polymer composition comprising: (A) 35-58 wt% of polyamide 6 having a relative solvent viscosity (RSV) of 2.5 or more as measured in 90% formic acid; (B) 2 to 10 wt% of a maleic anhydride grafted polypropylene having: i) an MFR (at190 DEG C 2.16 kg) of greater than 40 g / 10 min, and ii) a maleic anhydride concentration of 0.5 to 1.8 wt%, based on the weight of the maleic anhydride grafted polypropylene; (C) 32-63 wt% of a polypropylene composition having an MFR of less than 25 g / 10 min (at230 DEG C 2.16 kg) wherein when the amount of polyamide 6 is less than 45 wt%, the polypropylene composition comprises more than 80 wt% of one or more heterophasic propylene copolymers based on the weight of the polypropylene composition wherein the wt% of polymers in (A), (B) and (C) are defined based on the combined weight of (A), (B) and (C). The invention also relates to an extruded polymer composition. The invention also relates to an article comprising the composition according to the invention and a process for preparing the article, and to extruded and blown films comprising the composition according to the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polymer composition comprising polyamide 6, maleic anhydride grafted polypropylene and a polypropylene composition. Furthermore, the present invention relates to an extruded polymer composition, an article comprising said composition, a process for preparing said article, and both extruded and blown films comprising the composition of the invention. Background Art

[0002] In barrier packaging applications, sufficient barrier is required to minimize the penetration of oxygen (non-polar) and water vapor (polar) into the package. The role of barrier properties is to extend the shelf life of packaged foods or goods that are more sensitive to both oxygen and moisture. Barrier packaging products usually have a multi-layer structure made of multiple materials. There is no single single material that can provide a good barrier to both oxygen and water vapor. These multi-material packaging products are difficult to recycle. Most end up incinerated or landfilled.

[0003] Conventional non-barrier packaging applications, as opposed to barrier packaging, represent the majority of packaging applications. They are suitable for food or goods whose shelf life is not very sensitive to both oxygen and moisture. For these types of packaging, there is a strong trend towards single-material solutions for recycling purposes. However, due to food contact requirements, even high-quality recycled materials are difficult to reuse for most of these packaged products. Although one can sandwich recycled materials between two layers of virgin material, non-polar and polar impurities in the recycled materials can still penetrate into the packaged food or goods through the virgin material layers. As mentioned earlier, there is no single single material that can provide a good barrier to both polar and non-polar impurities.

[0004] "Single material product" according to this specification means that each part of the product is made of the same single material which may be a homopolymer, a copolymer or a polymer blend or composition comprising several components.

[0005] In a completely different area, namely industrial films and technical textile applications, multiple materials are coextruded, mixed, cowoven and / or laminated to achieve the desired properties, such as dimensional stability (e.g., with polypropylene or polyester), heat resistance (e.g., with polyamide and polyester), and hydrolysis and chemical resistance (e.g., with polyamide and propylene). These industrial products are easier to collect and recycle than consumer packaging, and ideally, the recycled materials should be used again in the same application to become a true cradle-to-cradle cycle. In order to achieve cradle-to-cradle circularity, a single material must be used and the single material must have comparable properties to current multiple material solutions.

[0006] Just as metal alloys are created to combine the performance advantages of different types of metals, making high-quality polymer alloys is an effective solution to combine the advantages of different polymers. In order to achieve the above-mentioned desired properties, the polymer alloy must contain both polar components such as polyamide and non-polar components such as polypropylene. This type of alloy belongs to immiscible polymer blends. Examples of polymer blends can be found in EP 3670131A1 of the present inventors.

[0007] Generally, the morphology of polymer blends can be classified into two typical categories: i) a matrix with dispersed droplet morphology and ii) a co-continuous morphology.

[0008] In a matrix with dispersed droplet morphology, the minor component is dispersed in the matrix formed by the major component (i.e., islands-in-the-sea morphology). This is the most common morphology of immiscible polymer blends. This is because the droplet lifetime (how long the morphology can stay in the melt) is longer than that of the fibrous structure to obtain a stable network structure in a high interfacial tension system.

[0009] In the co-continuous morphology, the mixed components show ordered or sometimes entangled fibrous structures. This is the most common morphology of miscible polymer blends. This is because the fiber-to-fiber lifetime is longer than the droplet lifetime in low interfacial tension systems. Blending polymers with the same dipole properties, such as blending polypropylene with high-density polyethylene, is a miscible blend.

[0010] On the other hand, co-continuous morphology is highly desirable for immiscible polymer blends as it allows all polymer components to function at their maximum level. Instabilities are a major challenge as high interfacial tensions will drive the system towards smaller interfacial areas. Long, thin fiber-like structures will break, shrink or coarsen into droplet form during melting.

[0011] Immiscible polymer blends are very difficult to achieve and maintain a majority of the co-continuous phase at the level of the polymer blend itself. This is a very sensitive balance. Any small change in polymer composition and processing conditions can change the morphology back to a matrix with dispersed droplets.

[0012] Therefore, there is a need for immiscible polymers in which all components can optimally contribute their property advantages in extruded and optionally shaped form. Summary of the invention

[0013] It is an object of the present invention to provide an improved immiscible polymer composition.

[0014] Another object of the present invention is to provide polymer compositions having good polar and non-polar barrier properties in extruded and optionally shaped articles.

[0015] Another object of the present invention is to provide a polymer composition which exhibits higher heat resistance than polypropylene in extruded and optionally shaped articles.

[0016] Another object of the present invention is to provide an improved polymer composition which simultaneously exhibits the property advantages of both polyamide 6 and polypropylene in extrusion and optionally in shaped articles.

[0017] Another object of the present invention is to provide polymer compositions which retain good properties in extruded and optionally shaped articles after recycling.

[0018] In a first aspect, the present invention relates to a polymer composition comprising:

[0019] (A) between 35 and 58 wt% polyamide 6 having a relative solvent viscosity (RSV) of 2.5 or more measured in 90% formic acid;

[0020] (B) between 2 and 10 wt% maleic anhydride grafted polypropylene having: i) an MFR (@190°C 2.16 kg) above 40 g / 10 min, and ii) a maleic anhydride concentration of 0.5 to 1.8 wt% based on the weight of the maleic anhydride grafted polypropylene;

[0021] (C) between 32 and 63 wt% of a polypropylene composition having a MFR of less than 25 g / 10 min (@ 230°C 2.16 kg), wherein when the amount of polyamide 6 is less than 45 wt%, the polypropylene composition comprises more than 80 wt% of one or more heterophasic propylene copolymers based on the weight of the polypropylene composition,

[0022] wherein the wt % of polymers in (A), (B) and (C) are defined based on the combined weight of (A), (B) and (C).

[0023] In a second aspect, the present invention relates to an extruded and optionally shaped polymer composition, wherein the polymer composition is a polymer composition according to the first aspect.

[0024] In a third aspect, the invention relates to an article comprising the composition according to the first aspect.

[0025] In a fourth aspect, the invention relates to a method of making an article according to the second aspect.

[0026] In a fifth aspect, the present invention relates to an extruded film comprising the composition according to the first aspect.

[0027] In a sixth aspect, the present invention relates to a blown film comprising the composition according to the first aspect.

[0028] The embodiments of the first aspect of the invention as a polymer composition (also referred to as an alloy, polymer alloy or plastic alloy; or a blend, plastic blend or polymer blend) are correspondingly applicable to the extruded and optionally shaped polymer composition according to the second aspect, the article according to the third aspect and the method according to the fourth aspect.

[0029] The present inventors have observed that polymer alloys which are combinations of very specific polymers with very specific properties, namely A) polyamide 6 with certain properties, B) polypropylene grafted with a high concentration of maleic anhydride with certain properties and C) a polypropylene composition with certain properties provide the desired properties. It was surprisingly found that the material combination after extrusion and optional forming has both a high oxygen barrier and a high moisture (water vapor) barrier. It was further surprisingly found that these materials have a higher heat resistance than polypropylene. It also combines the excellent properties of both polyamide and polypropylene, namely high tensile modulus and strength, good impact resistance, good heat resistance, high wear resistance and low friction and high non-polar substance barrier properties of the polyamide phase; having low density, high fatigue resistance, very low hygroscopicity, very low dielectric constant and very high polar substance barrier with the phase of polypropylene.

[0030] Without wishing to be bound by theory, the inventors believe that the low hot air shrinkage and high oxygen barrier achieved at 180°C indicate that the extruded plastic article has achieved the performance advantages of polyamide; while the high water vapor barrier achieved indicates that the extruded and optionally formed plastic article has achieved the performance advantages of polypropylene. These qualities of the extruded plastic article indicate that the polyamide 6 is not in the dispersed droplet phase and the polypropylene is not in the dispersed droplet phase.

[0031] Furthermore, when the extruded and optionally shaped plastic articles made from the polymer composition according to the invention are recycled and reprocessed into new plastic articles, the above-mentioned performance advantages are still maintained. This indicates that when the molecular orientation is maintained, the (co) continuous morphology is maintained.

[0032] Therefore, the inventors believe that the immiscible polymer blend composition according to the present invention can maintain a matrix morphology with dispersed droplets. However, when it is extruded and optionally formed, the molecules begin to orient in the flow direction of the molten polymer, and the phases of the droplets will be more easily oriented, then connected and become at least partially continuous fibrous or layered structures. After the polymer form cools and solidifies, the molecular orientation will remain, and therefore the (co) continuous morphology will remain in the final product. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The effect of temperature on the storage modulus of E2A samples formed by non-oriented processing and oriented processing is shown. DETAILED DESCRIPTION

[0034] Polymer composition

[0035] As mentioned above, the present invention relates in a first aspect to a polymer composition comprising:

[0036] (A) between 35 and 58 wt% polyamide 6 having a relative solvent viscosity (RSV) of 2.5 or more measured in 90% formic acid;

[0037] (B) between 2 and 10 wt% maleic anhydride grafted polypropylene having: i) an MFR (@190°C 2.16 kg) above 40 g / 10 min, and ii) a maleic anhydride concentration of 0.5 to 1.8 wt% based on the weight of the maleic anhydride grafted polypropylene;

[0038] (C) between 32 and 63 wt% of a polypropylene composition having a MFR of less than 25 g / 10 min (@ 230°C 2.16 kg), wherein when the amount of polyamide 6 is less than 45 wt%, the polypropylene composition comprises more than 80 wt% of one or more heterophasic propylene copolymers based on the weight of the polypropylene composition,

[0039] wherein the wt % of polymers in (A), (B) and (C) are defined based on the combined weight of (A), (B) and (C).

[0040] It should be noted that when it is read as "between 35 and 58 wt %", 35 and 58 wt % are included, and this can also be written as "35-58 wt %". This also applies to all similar references to ranges throughout this specification.

[0041] Polymer compositions according to the present invention can also be defined as polymer alloys or alloys. The polymer alloys or alloys used in this specification refer to materials similar to metal alloys, in which at least two different macromolecular substances (i.e. polymers or copolymers) are blended, excluding polymer additives. (Polymer) alloys according to this specification specifically refer to immiscible blends that exhibit (at least two blend components) at least two phases but have low interfacial tension. Preferably, each phase is mixed to such an extent that the inhomogeneity caused by different phases is on a sufficiently small scale that it is not obvious in use.

[0042] In one embodiment, the polymer composition will consist of (A), (B) and (C), in other words, the combined weight of (A), (B) and (C) forms 100 wt% of the polymer composition. In another embodiment, in addition to (A), (B) and (C), the polymer composition will contain other components, such as fillers. In other words, the combined weight of (A), (B) and (C) forms <100 wt% of the polymer composition, such as 60 wt% or more, 70 wt% or more, 80 wt% or more, 90 wt% or more, 95 wt% or more, 98 wt% or more, 99 wt% or more.

[0043] In one embodiment, the polymer composition comprises:

[0044] (A) between 35 and 50 wt % polyamide 6 having a relative solvent viscosity (RSV) of 2.5 or more measured in 90 % formic acid;

[0045] (B) between 2 and 10 wt% maleic anhydride grafted polypropylene having: i) an MFR (@190°C 2.16 kg) above 40 g / 10 min, and ii) a maleic anhydride concentration of 0.5 to 1.8 wt% based on the weight of the maleic anhydride grafted polypropylene;

[0046] (C) a polypropylene composition having a MFR of less than 10 g / 10 min (@ 230°C 2.16 kg) between 40 and 63 wt%, wherein when the amount of polyamide 6 is less than 45 wt%, the polypropylene composition comprises more than 80 wt% of one or more heterophasic propylene copolymers based on the weight of the polypropylene composition, preferably, wherein when the amount of polyamide 6 is less than 45 wt%, the polymer composition consists of one or more heterophasic propylene copolymers,

[0047] wherein the wt % of polymers in (A), (B) and (C) are defined based on the combined weight of (A), (B) and (C).

[0048] In another embodiment, the polymer composition comprises:

[0049] (A) between 36 and 56 wt% polyamide 6 having a relative solvent viscosity (RSV) of 2.5 or more measured in 90% formic acid;

[0050] (B) between 2 and 10 wt% maleic anhydride grafted polypropylene having: i) an MFR (@190°C 2.16 kg) above 40 g / 10 min, and ii) a maleic anhydride concentration of 0.5 to 1.8 wt% based on the weight of the maleic anhydride grafted polypropylene;

[0051] (C) between 34 and 62 wt% of a polypropylene composition having a MFR less than 10 g / 10 min (@ 230 °C 2.16 kg), wherein the polypropylene composition comprises more than 80 wt% of one or more heterophasic propylene copolymers based on the weight of the polypropylene composition;

[0052] wherein the wt % of polymers in (A), (B) and (C) are defined based on the combined weight of (A), (B) and (C).

[0053] In one embodiment, the polymer composition has a density measured according to ISO 1183-1:2019 (Method A - Dipping Method) of 0.97 to 1.02 g / cm 3 , preferably 0.97~1.00g / cm 3 This density is beneficial when articles made from the polymer composition are to be recycled, as the articles will float in (unsalted) water and will be easily separated from most other engineering polymers which have a density higher than water. 3 Polyolefin polymer separation. At a density of 0.97g / cm 3 In hot water at 80°C, the polyolefin will still float, whereas the polymer composition according to the invention will start to sink.

[0054] Each component will be discussed separately below.

[0055] Component A

[0056] Polyamide 6 as used in this specification refers to nylon 6 or polycaprolactam. Nylon 6 is synthesized by ring-opening polymerization of caprolactam. Caprolactam has 6 carbons, hence nylon 6.

[0057] The medium to high viscosity of polyamide 6, defined by a RSV of 2.5 or above, advantageously allows for the manufacture of fast cycle injection molded or extruded articles, especially medium to low tenacity fibers, from the polymer composition.

[0058] In one embodiment, the polyamide 6 has a relative solvent viscosity (RSV) measured in 90% formic acid of 2.5 to 2.7.

[0059] In one embodiment, the relative solvent viscosity (RSV) of polyamide 6 measured in 90% formic acid is above 2.7, which is preferably used when the plastic article is injection or blow molded into, for example, a main plate, manifold, container or bottle, or extruded into, for example, cast film, blown film, sheet, profile, tube, foam and especially the smallest medium to high tenacity fibers.

[0060] Component B

[0061] Component B is a polymer composition comprising one or more ultra-low viscosity functionalized propylene polymers (MA-g-PP) onto which a relatively large amount of maleic anhydride is grafted. It has the function of reducing the interfacial tension between components (A) and (C) and chemically bonding component (A), thus being dispersed (defuse) into (C) as a matrix phase. In the context of this application, ultra-low viscosity means an MFR higher than 40 g / 10 min (@190°C 2.16 kg), preferably higher than 50 g / 10 min.

[0062] Maleic anhydride is preferred because maleic anhydride, as the simplest cyclic anhydride, generates a strong covalent bond (imide bond) after reacting with the amine end groups of the polyamide.

[0063] Several types of MA-g-PP are available, these are generally defined by the following features: i) MFR (g / 10min@190°C), ii) weight percentage of maleic anhydride (MA), iii) melting peak temperature; and iv) melting enthalpy. The MFR may, for example, be in the range between 40 and 100 g / 10min or may be higher than 100 g / 10min. The MA content may be, for example, 0.5 wt%, 0.8 wt%, 1.0 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt% or 1.8 wt%. Any other value between 0.5 and 1.8 wt% is also possible. In one embodiment, the MA-g-PP used for component B has an MFR higher than 50 g / 10min, preferably higher than 60 g / 10min.

[0064] In one embodiment, the DSC melting peak temperature of the second heating scan of the MA-g-PP for component B at a heating rate of 20 K / min is between 130° C. and 165° C., and the normalized melting enthalpy is between 5 and 100 J / g. The melting peak temperature may be any temperature within the range of 130 to 165° C., and the normalized melting enthalpy may be between 5 and 100 J / g.

[0065] Melting peak temperature and melting enthalpy are taken from DSC measurements.The melting enthalpy is computer calculated by integrating the area between the endotherm and the baseline of the second heating scan in the temperature range between 80°C and 180°C.

[0066] In another embodiment, component (B) consists of one or more MA-g-PPs, and the average MA concentration of component (B) is 0.8-1.5 wt%. This is calculated by dividing the total weight of MA by the total weight of component (B).

[0067] The exact amount of component (B), i.e., MA-g-PP, in wt % based on the combined weight of components (A), (B) and (C), is determined by the desired total MA concentration (the "total MA concentration limit") based on the combined weight of components (A), (B) and (C) and the average MA concentration in component (B).

[0068]

[0069] In one embodiment, the total MA concentration of the polymer composition is less than 0.18 wt%, preferably less than 0.15 wt%, more preferably less than 0.1 wt%, based on the combined weight of (A), (B) and (C). Too high MA concentration will hinder the performance of the polyamide phase.

[0070] In another embodiment, the MA concentration of the polymer composition is greater than 0.01 wt%, preferably 0.02 wt% or more based on the combined weight of (A), (B) and (C). Too low a MA concentration cannot sufficiently reduce the interfacial tension between the PP and PA polyamide phases and leads to phase separation.

[0071] Component C

[0072] Component C is a polymer composition comprising one or more propylene-containing polymers, such as polypropylene homopolymers; polypropylene random copolymers; polypropylene heterophasic copolymers having a homopolymer or random copolymer matrix with a dispersed rubbery copolymer phase; and elastomer-modified polypropylene formed by blending / reacting polypropylene with olefin elastomers such as EPDM, EPR, EVA and SBS.

[0073] It should be noted that any MA-g-PP in component (B) is excluded from component (C). Nevertheless, the polymer composition of component (C) may contain other MA-grafted PPs, for example other MA-grafted PPs with higher viscosity and / or lower MA concentration than specified in (B). High viscosity PP grafted with low concentration of MA can improve the mixing effect of component (C), which will lead to improved mechanical properties of extruded articles.

[0074] All the polypropylene present in the polymer composition according to this invention is either the maleic anhydride grafted polypropylene (MA-g-PP) belonging to (B) or is comprised in the polypropylene composition in (C).

[0075] In one embodiment, when the RSV of PA 6 is lower than 3.0, the MFR of the polypropylene composition in (C) is lower than 25 g / 10 min (@230°C 2.16 kg), preferably lower than 20 g / 10 min.

[0076] In another embodiment, when the RSV of PA 6 is above 3.0, the MFR of the polypropylene composition in (C) is less than 10 g / 10 min (@230°C 2.16 kg), preferably less than 6 g / 10 min.

[0077] To achieve the best mix between (A) and (C), the higher the RSV of PA6 (A), the lower the MFR (reflecting higher viscosity) of (C) should be. Higher viscosity PA6 will be more difficult to break into smaller droplets or thinner fibrous or lamellar phases in the lower viscosity PP matrix.

[0078] In one embodiment the MFR of the polypropylene composition in (C) is less than 10 g / 10 min (@230°C 2.16 kg).

[0079] As mentioned above, the claimed range of component A (polyamide 6) can vary between 35 wt% and 58 wt%. However, the inventors have observed that when the amount of polyamide 6 in the polymer composition is less than 45 wt% (meaning that the polyamide 6 is definitely a minority phase by volume compared to the polypropylene phase), the polypropylene composition in (C) must comprise more than 80 wt% of one or more heterophasic propylene copolymers to ensure that the properties of the polyamide 6 are not hampered in the extrusion and optionally shaped article due to a good dispersion of the droplet phase in the polypropylene polymer matrix.

[0080] In one embodiment, when the amount of polyamide 6 in the polymer composition is less than 45 wt%, the polypropylene composition in (C) comprises more than 85 wt%, preferably more than 90 wt%, preferably more than 95 wt%, based on the weight of the polypropylene composition, of one or more heterophasic propylene copolymers. In a specific embodiment, when the amount of polyamide 6 in the polymer composition is less than 45 wt%, the polypropylene composition in (C) consists of one or more heterophasic propylene copolymers.

[0081] When the amount of polyamide 6 in the polymer composition is above 45 wt-%, for example between 45 and 58 wt-%, the polypropylene composition in (C) may still comprise or consist of one or more heterophasic propylene copolymers, but it may also comprise or consist of one or more other types of polypropylene, without the polypropylene properties being hampered in the extrusion and optionally shaped article due to the droplet phase dispersion in the polyamide polymer matrix.

[0082] As used in this specification, heterophasic propylene copolymers refer to copolymers having essentially at least a two-phase structure, consisting of a propylene-based semi-crystalline matrix and a dispersed elastomeric phase, typically ethylene-propylene rubber (EPR). These polypropylene copolymers are typically prepared in one or more reactors by polymerizing propylene in the presence of a catalyst system and then polymerizing a propylene-ethylene mixture; however, they can also be prepared by blending different (co)polymers. The resulting polymer material is heterophasic; studies have shown that there are four phases in heterophasic propylene-based copolymers: crystalline polypropylene, amorphous polypropylene, crystalline ethylene-propylene rubber (optional) and amorphous ethylene-propylene rubber. The advantage of such polymers is improved impact resistance, especially at lower temperatures.

[0083] In one embodiment the heterophasic propylene copolymer has:

[0084] a) a DSC melting peak temperature of the second heating scan at a heating rate of 20 K / min between 140°C and 170°C, preferably between 155°C and 168°C, and

[0085] b) a normalized melting enthalpy between 55 J / g and 95 J / g, preferably between 65 J / g and 90 J / g. The normalized melting enthalpy is taken between 80°C and 180°C.

[0086] In principle, a heterophasic propylene copolymer composition with a lower melting peak temperature and a lower melting enthalpy is more effective in preventing the PA6 phase from becoming a dispersed droplet phase in extrusion and optional formed products. On the other hand, the lower the better, because it will reduce the mechanical properties and heat resistance of the polypropylene phase at the same time.

[0087] More than one heterophasic propylene copolymer may be present in the polymer composition in (C). In this case the combined composition of these heterophasic propylene copolymers may have the features described above in a) and b).

[0088] Optional other components

[0089] The polymer composition according to the present invention may contain other components in addition to (A), (B) and (C). These components are usually inorganic and organic fillers added to the polymer composition. Typical fillers include, but are not limited to, glass beads, glass fibers and carbon fibers as reinforcing fillers; talc or magnesium as thickeners to reduce warping and sinking on thick walls; calcium carbonate as a thermal stabilizer; micas such as muscovite or phlogopite for improving rigidity and maintaining toughness; silicate mineral powders such as kaolinite and wollastonite for low deformation rigid formed parts; flame retardant fillers such as melamine cyanurate (MeCy), carbon black, carbon nanotubes (CNT), aluminum hydroxide (ATH) and phosphates.

[0090] Extruded and optionally shaped polymer composition

[0091] As mentioned above, the present invention in a second aspect relates to an extruded and optionally shaped polymer composition, wherein the polymer composition is a polymer composition according to the first aspect. The formed plastic article exhibits strong polyamide properties, such as high oxygen (or other non-polar substances) barrier and higher heat resistance, while still maintaining strong polypropylene properties, such as high water vapor (or other polar substances) barrier.

[0092] The inventors speculate that, in a first aspect, the preparation of the polymer composition, due to the presence of component (B), the interfacial tension between the polypropylene and polyamide phases is sufficiently low to keep the polyamide phase well dispersed as small droplets in the polypropylene phase as the main phase by volume. And in a second aspect, when the polymer composition is extruded and optionally formed into an article, the polymer molecules are oriented to a certain extent along the flow direction of the viscous extrudate, wherein the droplet phase is oriented, stretched, and connected at least in some areas, thus changing to an at least partially continuous fibrous or lamellar structure. When the molecular orientation is maintained, the continuous structure is maintained.

[0093] To show this effect in the experimental section, data for compression molded (non-oriented molecules) samples are also presented, which clearly show that the storage modulus is close to zero below 180°C, while for injection molded (partially oriented molecules) polymer compositions, the storage modulus is not close to zero at 180°C, even when the same polymer composition is used.

[0094] The polymer composition may be in the form of pellets or granules. In this form, it can be stably stored for subsequent extrusion and optional shaping steps.

[0095] The extruded and optionally shaped polymer composition according to the invention can be produced by providing more than 75 wt% of the polymer composition according to the invention and then combining (e.g. by dry blending) this composition with e.g. another PA6 (e.g. according to component (A)) or another polypropylene composition (e.g. according to component (C)) before extrusion and optional shaping. The total fraction of PA6 in the final blend should be between 35 and 58 wt%.

[0096] Thus, in an embodiment of the extruded and optionally shaped polymer composition, the polymer composition comprises more than 75 wt% of the polymer composition according to the first aspect of the invention. The remaining up to 25 wt% may comprise or consist of polyamide 6 or a polypropylene composition, preferably PA6 having a relative solvent viscosity (RSV) of more than 2.5 measured in 90% formic acid, and a polypropylene composition having an MFR of less than 25 g / 10 min (@230° C. 2.16 kg). In other words, the PA6 may be a PA6 according to (A), and the polypropylene composition may be a polypropylene composition according to (C).

[0097] In one embodiment of the second aspect, the extruded polymer composition is a film having a thickness between 1 micrometer and 250 micrometers. For example, it can be a film, such as a blown film, having a thickness of about 50 micrometers, such as 50 micrometers.

[0098] In another embodiment, the extruded polymer composition is a blown film having a thickness of 50 microns and a shrinkage of at most 5% in the MD and TD directions after being placed in an oven at 180° C. for 2 minutes. The shrinkage can be determined by a hot air shrinkage (HAS) test as described below. For example, the shrinkage can be at most 5.0%, or less than 5.0%, at most 4.0%, less than 4.0%, at most 3.0%.

[0099] In one embodiment of the second aspect, the extruded polymer composition is a sheet having a thickness greater than 250 microns.

[0100] In one embodiment of the second aspect, the extruded polymer composition is a foamed sheet.

[0101] In one embodiment of the second aspect, the extruded and then optionally shaped polymer composition is a blow molded or injection molded or thermoformed article, such as a bottle, a container or a panel.

[0102] In another embodiment, the oxygen permeability of the extruded and optionally shaped polymer composition measured at 23° C. and 50% relative humidity according to ASTM F1927-20 is less than 12 mL*mm / (mm 2 In certain embodiments, the oxygen permeability measured at 23°C and 50% relative humidity according to ASTM F1927-20 is less than 8 mL*mm / (mm 2 *days). Oxygen permeability values ​​are determined by the transmission rate on a 50 micron film measured at 23°C and 50% relative humidity according to ASTM F1927-20.

[0103] In another embodiment, the water vapor permeability of the extruded and optionally shaped polymer composition measured at 23° C. and 85% relative humidity according to ASTM F1249-20 is less than 0.25 g*mm / (mm 2 * days). In certain embodiments, the water vapor permeability measured according to ASTM F1249-20 at 23°C and 85% relative humidity is less than 0.18 g*mm / (mm 2 * days). Water vapor permeability values ​​are determined by transmission rate on 50 micron films measured at 23°C and 85% relative humidity according to ASTM F1249-20.

[0104] In another embodiment, the extruded and optionally shaped polymer composition has an oxygen permeability of less than 12 mL*mm / (mm 2 *day), preferably less than 8mL*mm / (mm 2 * days), and the water vapor permeability of the extruded and optionally shaped polymer composition measured at 23°C and 85% relative humidity according to ASTM F1249-20 is less than 0.25 g*mm / (mm 2 *day), preferably less than 0.18g*mm / (mm 2 *sky).

[0105] In an embodiment of the second aspect, the extruded polymer composition is a monofilament or multifilament having the performance advantages of polyamide, such as higher tensile strength, higher flexural resilience, higher temperature resistance and higher wear resistance, and the performance advantages of polypropylene, such as high dimensional stability, low dielectric constant and high chemical resistance.

[0106] In an embodiment of the second aspect, the extruded polymer composition is a monofilament that is further extruded in a fused deposition modeling (FDM) process to form a 3D printed part. The 3D printed part exhibits the performance advantages of both polyamide and polypropylene.

[0107] Without wishing to be bound by theory, the inventors believe that the extruded polymer composition according to the present invention will have low oxygen permeability (OP) and low water vapor permeability (WVP) because both PA6 and PP are in a continuous phase, which is achieved by the specific combination of polymers with specific properties disclosed in claim 1. Polyamide 6 is known to have good oxygen barrier properties, but poor water vapor barrier properties. In addition, polypropylene is known to have excellent water vapor barrier properties, but poor oxygen barrier properties. By extruding and / or forming the specific alloy according to the present invention into films, sheets and containers, the matrix PP phase maintains its continuous form to provide excellent water vapor barrier, while the initially dispersed droplets of the PA phase are oriented, stretched and eventually connected into at least partially continuous fibrous or lamellar microphases, which will contribute to a high barrier to non-polar substances such as oxygen. In addition to the barrier properties, the low hot air shrinkage at 180°C is a second evidence that the polyamide no longer exists as droplets dispersed in the matrix of the extruded and / or formed form.

[0108] Without wishing to be bound by theory, the inventors believe that the extruded and optionally shaped polymer composition according to the present invention may have an at least partially co-continuous phase morphology, wherein the PP remains as a continuous matrix phase, while the initially dispersed droplets of the PA phase are oriented, stretched and eventually connected into an at least partially continuous fibrous or lamellar microphase.

[0109] The extruded article according to the invention shows the same properties if it is formed directly after the polymer composition is formed or if the polymer composition has been stored within a standard shelf life of at least 2 years.

[0110] Products

[0111] As mentioned above, the present invention in a third aspect relates to an article comprising the polymer composition according to the first aspect.

[0112] In one embodiment, the article is a tube, profile or jacket covering an electric wire or cable.These articles exhibit the performance advantages of both polyamide and polypropylene.

[0113] Method for preparing the article

[0114] As described above, the present invention in a fourth aspect relates to a method for preparing an article according to the third aspect, which includes 3D printing, film or sheet extrusion, monofilament or multifilament extrusion, foam or tube or profile extrusion, extrusion blow molding, injection blow molding, stretch blow molding, thermoforming, injection molding or extrusion coating.

[0115] In one embodiment, the method comprises injection moulding, blow moulding or thermoforming the polymer composition according to the first aspect of the invention.

[0116] Extruded Film

[0117] As mentioned above, the present invention in a fifth aspect relates to an extruded film having a thickness between 1 and 250 microns comprising more than 75 wt% of the polymer composition according to the first aspect of the invention.

[0118] Blown Film

[0119] As mentioned above, the present invention in a sixth aspect relates to a blown film having a thickness of 50 microns and a shrinkage of at most 5% in MD and TD directions after being placed in an oven at 180°C for 2 minutes, comprising 75 wt% or more of the polymer composition according to the first aspect of the present invention.

[0120] From a study of the drawings, the disclosure and the appended claims, other variations to the disclosed embodiments may be understood and implemented by those skilled in the art in practicing the claimed invention. In the claims, the word "comprising" does not exclude other elements or steps, and the indefinite article "a" or "an" does not exclude a plurality. The fact that certain measures are recited in mutually different dependent claims does not indicate that a combination of these measures cannot be used advantageously. The scope of the invention is defined by the appended claims. One or more objects of the invention are achieved by the appended claims.

[0121] Materials and methods

[0122] MFR

[0123] If not specified, the melt flow rate (MFR) is measured according to ISO 1133: 1-2011. There are two applicable conditions: 230°C, 2.16 kg for normal and high viscosity polyolefin polymers and 190°C, 2.16 kg for ultra-low viscosity polyolefin polymers.

[0124] DSC

[0125] If not otherwise specified, differential scanning calorimetry (DSC) was performed according to ASTM D3418-03. Slices of polymer particles (weight between 4 and 5 mg) were cut as specimens. Each specimen was heated from -20°C to 250°C at a heating rate of 20 K / min (first heating scan) to remove the thermal history. The sample was then kept at a temperature of 250°C for 5 minutes and then cooled from 250°C to -20°C at 20 K / min (cooling scan). The sample was then kept at a temperature of -20°C for 5 minutes. The sample was then heated again from -20°C to 250°C at a heating rate of 20 K / min (second heating scan).

[0126] DMA / Storage Modulus

[0127] The storage modulus describes the elastic properties of viscoelastic materials, usually made from polymer compositions. When a polymer article is melted, it becomes completely viscous and the storage modulus approaches zero.

[0128] In the present invention, if the storage modulus above the PP melting peak (above 170°C) is close to zero, it is directly proved that the PA phase in the polymer composition remains as a dispersed droplet phase. Vice versa, the higher the storage modulus level above the PP melting peak (above 170°C), the more PA forms a continuous phase.

[0129] The storage modulus at elevated temperature was determined by DMA measurement. If not specified otherwise, dynamic mechanical analysis (DMA) was performed according to ISO 6721-4. The sample was subjected to a thermal ramp from 27°C to 190°C at a heating rate of 3°C / min, a frequency of 1 Hz and an amplitude of 10 μm.

[0130] DMA samples were prepared as follows. Compression molded samples were prepared by compressing 0.5-0.6 g of polymer pellets at 230°C with a force of 50 kN for 5 minutes to form 30×30×0.5 mm thin plates. The compressed samples were then removed and quenched by dropping into room temperature water. Prior to DMA measurements, 20×2×0.5 mm dog-bone shaped samples were cut from the plates and dried in a vacuum oven at 80°C for 6 hours.

[0131] Injection molded samples were prepared by injection molding 80 × 80 × 1.0 mm plaques at a mold temperature of 60 ° C. Before DMA measurement, 20 × 2 × 1.0 mm dog-bone shaped samples were cut along the polymer flow direction and dried in a vacuum oven at 80 ° C for 6 h.

[0132] Blown Film

[0133] Blown film samples were prepared in a Collin Blown Film Unit BL 200. The film die diameter was 94.2 mm and the die gap was 0.8 mm. The extrusion temperature was 260° C. The blow-up ratio was 2.5-2.6. The film thickness was about 50 microns.

[0134] OTR

[0135] If not otherwise specified, the oxygen transmission rate (OTR) is measured at 23°C and 50% relative humidity according to ASTM F1927-20. The unit of oxygen transmission rate is ml / (m 2 · days). OTR depends on the thickness of the measured sample.

[0136] OP

[0137] When the sample is made of a homogeneous single material, the measured OTR can be converted to an oxygen permeability (OP) value according to the following equation:

[0138]

[0139] The unit of OP is ml·mm / (m 2 · days). Physically, OP defines the oxygen permeation properties of a homogeneous single material. OP does not depend on the thickness of the measured sample. Instead, OP is used to predict the OTR of a plastic film (sheet or wall) with a given thickness, assuming that the film (sheet or wall) is not further stretched in the solid state.

[0140]

[0141] WVTR

[0142] If not otherwise specified, the water vapor transmission rate (WVTR) is measured at 23°C and 85% relative humidity according to ASTM F1249-20. The unit of water vapor transmission rate is g / (m 2 · days). WVTR depends on the thickness of the measured sample.

[0143] WVP

[0144] When the sample is made of a homogeneous single material, the measured WVTR can be converted into a water vapor permeability (WVP) value according to the following equation:

[0145]

[0146] The unit of WVP is g·mm / (m 2 · days). Physically, WVP defines the water vapor permeability properties of a homogeneous single material. WVP is independent of the thickness of the sample being measured. Instead, WVP is used to predict the WVTR of a plastic film (sheet or wall) of a given thickness, without further stretching of the film (sheet or wall) in the solid state.

[0147]

[0148] density

[0149] The density of the polymer composition is determined according to ISO 1183 by the immersion method.

[0150] HAS

[0151] The Film Hot Air Shrinkage (HAS) test compares the distance between specific marked points on a film sample before and after placing the film sample in a preheated drying oven at 180°C for 2 minutes.

[0152] Since OTR measurement is expensive and time-consuming, HAS is introduced as an effective alternative to test whether PA becomes the continuous phase in the film. If only PP is the continuous phase and PA remains as a droplet phase, the film will shrink significantly and melt at the edge under this test condition. This is because the melting peak of the PP phase is below 170°C.

[0153] The test is performed in the following manner:

[0154] On A4 0.5cm grid paper, draw a 30×30 grid square. Mark the four vertices of the square, the four midpoints of each side, and the center of the square. These nine points represent three vertical lines and three horizontal lines of equal length.

[0155] A4 size 50 micron blown film sample is placed on the grid and nine points are marked on the film sample. The film sample is then placed on the top of a stainless steel plate covered with Teflon paper. The film sample is placed in a drying oven preheated at 180°C for 2 minutes. After taking it out from the oven, the film sample is cooled to room temperature. The film sample is placed on the grid paper again, and the maximum displacement point is used to calculate the shrinkage (in %) in the horizontal and vertical directions. For each film sample, the test is repeated twice. In addition, a visual inspection is performed to see if the film is melted at the edge.

[0156] Material

[0157] Component (A)

[0158] The polyamide (PA) used in the examples is a PA6 homopolymer and has a relative viscosity index of 3.0-3.2 measured in 90% formic acid.

[0159] Component (B)

[0160] The maleic anhydride grafted functionalized propylene (co)polymers and / or elastomers (MA-g-PP) are listed in Table 1. MFR was measured at 190°C, 2.16 kg. The normalized melting enthalpy was taken between 80°C and 180°C.

[0161] Table 1: Characterization of different types of MA grafted polypropylene

[0162] Types of MAH-grafted PP MFR(g / 10min@190℃) MA wt% Melting peak(℃) Enthalpy (J / g) I >100 1.0 131~140 60~70 II 50~100 1.0 158~165 89~99 III >100 1.2 138~141 6~10 IV >100 2.0 155~162 87~99

[0163] Component (C)

[0164] The MFR of the heterophasic propylene copolymer (Hetero-B-cPP) is 0.7-1.2 g / 10 min@230°C, the melting peak of the second heating scan of DSC is 162-165°C, and the normalized melting enthalpy is 79-88 J / g. The normalized melting enthalpy is taken between 80°C and 180°C.

[0165] The random propylene copolymer (Random-cPP) has an MFR of 7.5 to 8.5 g / 10 min@230°C, a melting peak in the second DSC melting scan of 147 to 149°C, and a normalized melting enthalpy of 75 to 78 J / g. The normalized melting enthalpy is taken between 80°C and 180°C.

[0166] The MFR of propylene homopolymer (Homo-PP) is 2.0 g / 10 min@230°C, the melting peak in the second DSC melting scan is 162-164°C, and the normalized melting enthalpy is 98-105 J / g. The normalized melting enthalpy is taken between 80°C and 180°C.

[0167] In addition, in some embodiments, a low anhydride concentrated compatibilizer (LAC) is present. The MFR of the LAC is 4.5-5.5 g / 10 min@230°C, the melting peak in the DSC second heating scan is 150-152°C, and the normalized melting enthalpy is 60-65 J / g. The normalized melting enthalpy is taken between 80°C and 180°C.

[0168] Composition preparation

[0169] Polymer compositions made of the polymers listed above were prepared by reactive compounding using a Coperion ZSK Mc18 twin-screw extruder. The polymers were first dry-blended according to the recipe and then extruded under a gently rising temperature profile starting at 190°C in zone 1 and gradually increasing to 210°C in zone 9. The processing parameters were then fine-tuned to keep the measured temperature of the melt between 275°C and 285°C and the die pressure fluctuations less than 5 bar. The polymer composition was then reprocessed at 800 rpm with a standard output of 6 kg / hour to achieve optimal homogeneity.

[0170] Example

[0171] The present invention is further illustrated based on the following examples, which are merely illustrative and are not to be construed as limiting the present invention.

[0172] Composition of the embodiment

[0173] Table 2 shows the composition of different examples. Table 2 shows (A) the amount of PA6, (B) the type (refer to the type of Table 1) and the amount of MA grafted polypropylene, and (C) the amount of other polypropylenes. The wt% indicated in the table is defined based on the combined weight of (A), (B) and (C). For Hetero-B-cPP, the wt% is mentioned between square brackets, which is defined based on the total weight of the polypropylene composition (C).

[0174] Table 2: Characterization of Examples

[0175]

[0176] The examples can be divided into two parts: part 1 of examples E1A-CE1I, and part 2 of examples E2A-CE2I and additionally E2J. These parts can be directly compared (e.g. E1A with E2A, E1B with E2B, etc.), where the examples of part 1 have a lower amount of PA in the polymer composition than the examples of part 2. The examples listed as "E" are examples according to the invention, while the examples listed as "CE" are comparative examples and are not according to the invention. Examples CE1C-CE1G are not according to the invention, since the amount of PA6 is less than 45 wt%, and the polypropylene composition does not comprise more than 80 wt% of one or more heterophasic propylene copolymers, based on the weight of the polypropylene composition. Examples CE1I and CE2I are not according to the invention, since the maleic anhydride concentration of the MA-grafted polypropylene type IV is 2.0 wt%, based on the weight of the maleic anhydride-grafted polypropylene, which is outside the claimed range. Furthermore, in CE2I, the total MA concentration in the polymer composition reaches 0.20 wt%, which is outside the claimed range.

[0177] Example E2J uses a composition of 100 wt% of E2A to be dry-blended with 25 wt% of PA6. The new polymer mixture E2J was not processed in a twin-screw extruder like the other examples, but was directly extruded on a blown film line to make a film sample. This sample was produced to test whether the initially dispersed PA phase droplets in the polymer composition according to the invention will become at least partially continuous fibrous or lamellar microphases when the molecules are oriented in the direction of the molten polymer flow, i.e. in a single-screw extruder and in the die of a blown film line. If this is the case, E2A should have very good mixing with the additional PA6 added. This mixing does not lead to separation of the PP phase from the PA phase. This results in E2J being a homogeneous film.

[0178] The second purpose of E2J was to verify whether the purpose of the invention is still achieved at the upper limit of the claimed range. The PA fraction in the new polymer mixture E2J was increased to 56 wt% by adding an additional 25 wt% of PA6 to 100 wt% of E2A. The PP fraction was reduced to 44 wt% and became a minority by weight. There was a risk that the PP phase might change from a continuous matrix to a dispersed droplet phase. The density of E2J was 1.02 g / cm 3 , which is the upper limit of the claimed range.

[0179] Hot Air Shrinkage Test (HAS)

[0180] Table 3 shows the results of the film hot air shrinkage test in the machine direction (MD) and transverse direction (TD), as well as the average in both directions. It further gives the qualitative visual results on the edges after exposure to heat. N means that the edges of the film are not melted. Y / N means that the edges of the film sample show some melting, and Y means that the edges of the film sample show obvious signs of melting around all edges.

[0181] To facilitate comparison, the film samples have the same sample code as the polymer composition used.

[0182] Table 3: Shrinkage results for 50 micron blown films made from polymer compositions according to Table 1

[0183]

[0184] As can be seen from Table 3, the examples according to the invention achieve an average shrinkage of up to 5%, while the comparative examples have a much higher average shrinkage (9.0 to 13.3). And all comparative examples melt at the edges. This shows that the heat resistance of the extruded and optionally shaped polymer composition according to the invention is improved.

[0185] CE1I and CE2I show that when the amount of maleic anhydride in the ultra-low viscosity MA-g-PP of component B is above 1.8 wt % based on the weight of the MA-g-PP, the extruded polymer composition does not achieve the desired heat resistance (measured by shrinkage).

[0186] The present inventors believe that this is because the comparative examples have only PP as a continuous phase, and PA remains as a droplet phase. Therefore, at 180°C, which is well above the melting peak temperature of PP, all samples shrink significantly and melt at the edges.

[0187] When comparing CE1I to E1A and E1B, CE1I uses the same PA6 and the same Hetero-B-cPP, with an even higher PA6 concentration (40 wt% vs. 36 wt%), but still shows poor HAS results and the film melts at the edges. This is direct evidence that component B with too high a maleic anhydride concentration (above 1.8 wt%, based on the weight of the MA-g-PP) will have a negative impact on achieving the objectives of the present invention.

[0188] When comparing CE1I and CE2I, CE2I increases the PA6 concentration from 40wt% to 50wt% and increases component B from 5wt% to 10wt%, which results in a maleic anhydride concentration of 0.2wt% in the total polymer composition. But it still has poor HAS results and the film melts at the edge. This is direct evidence that simply increasing the PA6 concentration and increasing the maleic anhydride concentration may not achieve the purpose of the present invention.

[0189] On the other hand, sample E2J has the best HAS result. This result indirectly proves that the PP phase in sample E2J is not segregated, otherwise the segregated PP phase will melt and shrink at 180 °C. However, another possibility that the PP phase in E2J has become dispersed droplets cannot be ruled out.

[0190] Oxygen permeability and water vapor permeability

[0191] According to the same speculation, the inventors believe that the examples according to the present invention will have both low oxygen permeability (OP) and low water vapor permeability (WVP). This is because the PP phase remains as a continuous phase, while the originally dispersed droplet PA phase changes into at least partially continuous fibrous or lamellar microphases during blown film extrusion. In contrast, the OP of the comparative examples will remain high despite the high percentage of PA in the composition. Table 4 shows the OP and WVP of different polymer compositions. The values ​​for LDPE, PP and PA6 represent generic values ​​representative of these polymer types and are calculated by the Innoform Permeation Calculator.

[0192] Table 4: Oxygen permeability and water vapor permeability

[0193] LDPE* PP* CE1C E1A E2A E2J PA6* OP 200.0 55.0 43.5 5.1 2.7 2.2 2.0 WVP 0.10 0.05 0.13 0.13 0.14 0.15 0.88

[0194] As can be seen from Table 4, Examples E1A, E2A and E2J according to the present invention provide a unique combination of low OP (high oxygen barrier) and low WVP (high moisture barrier), while Comparative Example CE1C has an OP almost 8 times higher than E1A despite a higher PA concentration (40 wt% vs. 36 wt% for E1A).

[0195] Significantly, although the PP fraction of E2J is reduced from 55 wt% to 44 wt% compared to E2A, its WVP is still very low. The good HAS, OP, WVP results of E2J confirm that the objectives of the present invention are achievable at the upper limit of the claimed range.

[0196] DMA storage modulus

[0197] Figure 1 The effect of temperature on the storage modulus of E2A samples formed by non-oriented and oriented processes is shown. Compression molding is a non-oriented process, while injection molding is an oriented process.

[0198] The black line represents the injection molded sample. A drop in the storage modulus can be seen around 180°C, after which it stabilizes again. This indicates that the PA phase in the injection molded sample is at least partially continuous, which improves the heat resistance properties of the sample.

[0199] The gray line represents the compression molded sample. The storage modulus is close to zero at 180 °C. It is assumed that the morphology of the compression molded sample is very close to that of the original polymer composition because both forms are not oriented. Therefore, the results indicate that the PA phase remains as a droplet phase dispersed in the PP matrix phase in the polymer composition.

[0200] Recycle

[0201] If both PP and PA are in the form of continuous phase in the polymer composition, after the alloy is melted again and again, it may disappear and turn back into a phase of PA droplets dispersed in the PP matrix. This will repeatedly cause performance problems after multiple cycles of processing and recycling.

[0202] The DMA storage modulus proves that this is not the case for the polymer composition according to the invention, since the polymer composition already has a matrix-droplet morphology from the outset. Therefore, the polymer composition according to the invention can be recycled. And the improved properties of the (extruded and optionally shaped) polymer composition according to the invention can also be achieved by the recycled polymer composition.

[0203] Blown film sample E1A was selected for recycling testing. E1A was selected because it has the lowest PA concentration (36 wt%) of all examples. More likely, the performance advantage of E1A may disappear after recycling.

[0204] method

[0205] First, 2 kg of blown film E1A was chopped into pieces. The pieces were then compression molded at 230 ° C with a force of 50 kN for 5 minutes to form a 300 × 300 × 2.0 mm plate. After that, the plate was chopped again into pieces that became suitable for processing in a twin-screw extruder. The suitable pieces were processed on a Coperion ZSK Mc18 twin-screw extruder with a gently rising temperature curve, where the temperature curve started from 190 ° C in zone 1 and gradually increased to 210 ° C in zone 9, with a rotation speed of 800 rpm and an output of 6 kg / hour. The recovered polymer was further processed on a Collin Blown Film Unit BL 200 to make a blown film according to the settings of the remaining blown film samples.

[0206] result

[0207] The blown film samples were further evaluated with HSA at 180°C: the average shrinkage was 3.5%; and the 2 * days). Both results are comparable to those of the E1A blown film. This confirms that the polymer composition can also achieve the purpose of the present invention after recycling.

Claims

1. A polymer composition comprising: (A) between 35 wt % and 58 wt % of polyamide 6 having a relative solvent viscosity (RSV) of 2.5 or more as measured in 90 % formic acid; (B) between 2 wt% and 10 wt% maleic anhydride grafted polypropylene having: i) an MFR (@190°C, 2.16 kg) above 40 g / 10 min, and ii) a maleic anhydride concentration of 0.5 to 1.8 wt% based on the weight of the maleic anhydride grafted polypropylene; (C) between 32 wt% and 63 wt% of a polypropylene composition having a MFR of less than 25 g / 10 min (@230°C, 2.16 kg), wherein when the amount of polyamide 6 is less than 45 wt%, the polypropylene composition comprises more than 80 wt% of one or more heterophasic propylene copolymers based on the weight of the polypropylene composition, wherein the wt% of the polymers in (A), (B) and (C) are defined based on the combined weight of (A), (B) and (C), preferably wherein all the polypropylene present in the polymer composition is the maleic anhydride grafted polypropylene in (B) or is included in the polypropylene composition in (C).

2. The polymer composition of claim 1, having a maleic anhydride concentration of less than 0.18 wt% based on the combined weight of (A), (B) and (C).

3. The polymer composition according to claim 1 or 2, wherein the relative solvent viscosity (RSV) of polyamide 6 measured in 90% formic acid is above 2.

7.

4. The polymer composition according to any one of the preceding claims, having a density measured according to ISO 1183-1:2019 (method A - immersion method) of 0.97 g / cm 3 and 1.02g / cm 3 between.

5. Polymer composition according to any of the preceding claims, wherein the one or more heterophasic propylene copolymers have: a) the DSC melting peak temperature of the second heating scan at a heating rate of 20 K / min is between 140° C. and 170° C., preferably between 158° C. and 168° C., and b) the normalized melting enthalpy taken from the second heating scan between 80°C and 180°C is between 55 J / g and 95 J / g, preferably between 65 J / g and 90 J / g.

6. An extruded and optionally shaped polymer composition, wherein the polymer composition comprises more than 75 wt% of the polymer composition according to any one of claims 1 to 5.

7. The extruded and optionally shaped polymer composition according to claim 6, further comprising less than 25 wt% of polyamide 6 having a relative solvent viscosity (RSV) of more than 2.5 measured in 90% formic acid, or less than 25 wt% of a polypropylene composition having an MFR of less than 25 g / 10 min (@230°C 2.16 kg).

8. An extruded and optionally shaped polymer composition according to claim 6 or 7, wherein the polymer composition is a polymer composition according to any one of claims 1 to 5.

9. An extruded and optionally shaped polymer composition according to any one of claims 6 to 8, having an oxygen permeability of less than 12 mL*mm / (mm 2 *day), preferably less than 8mL*mm / (mm 2 *sky).

10. An extruded and optionally shaped polymer composition according to any one of claims 6 to 9, having a water vapor permeability of less than 0.25 g*mm / (mm 2 *day), preferably less than 0.18g*mm / (mm 2 *sky).

11. An extruded film having a thickness between 1 and 250 micrometers, the extruded film comprising more than 75 wt% of the polymer composition according to any one of claims 1 to 5.

12. A blown film having a thickness of 50 micrometers and shrinkage of 5% or less in MD and TD directions after being placed in an oven at 180°C for 2 minutes, the blown film comprising 75 wt% or more of the polymer composition according to any one of claims 1 to 5.

13. An article comprising the polymer composition according to any one of claims 1 to 5.

14. A method for preparing an article according to claim 13, comprising 3D printing, film or sheet extrusion, monofilament or multifilament extrusion, foam or tube or profile extrusion, extrusion blow molding, injection blow molding, stretch blow molding, thermoforming, injection molding or extrusion coating.

Citation Information

Patent Citations

  • Polymer composition, method for preparing said composition, article comprising said composition and method for preparing said article

    EP3670131A1